Pengaruh Literasi Teknologi dan Pengembangan Inovasi Pendidikan Terhadap Minat Belajar Mahasiswa - Nur Eliza, Julia; Syevyilni Wisda, Rini (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This research aims to determine the influence of the application of technological literacy and the development of educational innovation on students' interest in learning at the Kerinci State Islamic Institute (IAIN). This research uses quantitative methods with a simple linear regression approach. Data was obtained from 120 respondents using a questionnaire. The sampling technique uses Random Sampling. The research results show that from the